EMILIA PRAETERMISSA MILNE-REDHEAD (ASTERACEAE): PHYTOCHEMICAL PROFILING AND CYTOTOXIC POTENTIAL - ODION, Emmanuel; EDET, Alexanander; AMBE , Daniel; OSIGWE, Chinyelu; ODIETE, Eravweroso Congrat (African Journal of Traditional, Complementary and Alternative Medicines, 2025)
Background: Emilia praetermissa Milne-Redhead, is a fast growing herb that is native to west and central Africa, the leaf is use in the treatment of ulcer, hernia, pain and tumor by traditional healers in these regions. It is explored in this study for its phytochemicals and cytotoxic activities. Materials and Methods: The powdered leaf was screened for phytochemicals using standard methods, while profiling of the methanol extract was done by both Gas Chromatography-Mass Spectrometry (GCMS) and High Pressure Liquid Chromatography (HPLC). Cytotoxic potential was evaluated using Raniceps raninus (Tadpole-fish) at varying doses (20-320 µg/mL) of the extract (methanol) and fractions (ethylacetate and dichloromethane). Results: Tannins, flavonoids, steroids, glycosides, alkaloids and saponins were revealed by the phytochemical screening. The GC-MS analysis identified thirty-three compounds, which include aziridine, benzaldehyde, benzofuran, carbazole, hydroquinone, isopropylidine, indole, piperidine, piperazine, pyrazole, pyridine, pyrrolidine and tetrazole derivatives. Twelve compounds were identified and quantified from the HPLC analysis; coumaric acid (10.2385 µg/ml), cresol (25.7350 ppm), ellagic acid (3.9547 µg/ml), ferulic acid (8.9514 µg/mL), isoflavone (22.7694 ppm), naringenin (14.1526 µg/mL), naringin (5.6179 µg/ml), pyrogallol (12.5850 µg/g), resveratrol (3.8639 ppm) and salicylic acid (17.4195 µg/mL) respectively. A dose of 160 µg/mL of the methanol extract significantly (P<0.05) resulted in (60.00 ± 5.78) % mortality rate within 90 minutes, and (100.00 ± 0.00) % mortality as the dose was double (320 µg/mL) after 120 minutes. Conclusion: These thus indicate the presence of phytochemicals in E. praetermissa leaf with cytotoxic potential.